The Current Application of LC-MS/MS in Pharmacokinetics of Traditional Chinese Medicines (Recent Three Years): A Systematic Review - Wang, Yang; Zhang, Lu; Gu, Shuang; Yin, Zhaorui; Shi, Zhe; Wang, Ping; Xu, Changhua (Current Drug Metabolism, 2020)
Background: With significant clinical effects, traditional Chinese medicine (TCM) has been attracting increasing interest of the world's scientific community. However, TCM contains immense amounts of chemical components. It is a great challenge to objectively evaluate the correlation between the in vivo process and the therapeutic effect of TCM. The purpose of this systematic review was to summarize the recent investigation (from 2017 to 2019) on preclinical pharmacokinetics (PK) of TCM via liquid chromatography coupled with mass spectrometry (LC-MS/MS). Methods: We reviewed the published articles regarding the PK of TCM by LC-MS/MS. In addition, we summarized information on PK parameter of bioactive components, single herb and traditional Chinese medicine prescriptions. Results: The vast majority of literature on preclinical PK of TCM uses single oral administration, the biological matrix is mostly rat plasma, and the main PK parameters include AUC, Cmax, Tmax and T1/2, etc. Conclusion: Although LC-MS/MS can be used for high-throughput analysis, the characterization of in vivo processes of TCM still has a long way. With the advantages of high sensitivity, high specificity and simple operation, the increasingly mature LC-MS/MS technology will play an important role in the PK study of TCM.
Keywords: pharmacokinetics